Characterization of cadmium sulfide nanorods prepared by the solvothermal process - Phuruangrat A. (2014)
Cadmium sulfide nanorods were successfully prepared from cadmium nitrate tetrahydrate and thiourea in ethylenediamine by 200 °C solvothermal reactions using hydroxyethyl cellulose (HEC) as a capping material. X-ray diffraction (XRD), selected area electron diffraction (SAED), and Raman spectroscopy showed that the products were hexagonal wurtzite CdS with the 1st and 2nd harmonic modes at 303.5 and 593.0 cm- 1, respectively. The intensity ratios of the 2nd to 1st harmonic modes were increased with their aspect ratios, due to the great strength of exciton-phonon coupling. By using scanning electron microscopy (SEM), transmission electron microscopy (TEM), high resolution TEM (HRTEM) and fast Fourier transformation (FFT), the products were in the shape of nanoparticles in the HEC-free solution, and became nanorods with higher aspect ratios in the HEC-added solutions - especially with longer reaction time. These nanorods were single crystals with growth in the [001] direction. © 2009 Elsevier B.V. All rights reserved.